2010
DOI: 10.1155/2010/138019
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Effects of Gammalin 20 on African Catfish (Clarias gariepinus)

Abstract: Clarias gariepinus fingerlings exposed to lethal and sublethal concentrations of Gammalin 20 were investigated in a renewal static bioassay with particular reference to behaviour, survival, and histopathological changes. Early symptoms of gammalin 20 lethal poisoning were, respiratory distress, increased physical activity, convulsions, erratic swimming, loss of equilibrium, and increased breathing activity. Behavioural response was dose dependent and decreased with decreased concentration. The 96-hour lethal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…It is quite apparent that the damage caused to the gills results in impairments in gaseous exchange capacity of the gills, which ultimately lead to respiratory distress. Similar view was presented by Rahman et al (2002); Omitoyin et al (2006) and Ezemonye and Ogbomida (2010) for the damage of gills in the fish treated with toxicants and support to present findings.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…It is quite apparent that the damage caused to the gills results in impairments in gaseous exchange capacity of the gills, which ultimately lead to respiratory distress. Similar view was presented by Rahman et al (2002); Omitoyin et al (2006) and Ezemonye and Ogbomida (2010) for the damage of gills in the fish treated with toxicants and support to present findings.…”
Section: Resultssupporting
confidence: 93%
“…Presence of fat vacuoles in the liver of treated fish showed evidence of fatty degeneration. Hepatocytes necrosis may be the results of inability of the fish to regenerate new hepatocytes (Ezemonye and Ogbomida, 2010). Necrosis occurred in the liver of exposed fish can also be related to the excessive burden of work for the detoxification of insecticide from the body.…”
Section: Resultsmentioning
confidence: 99%
“…Uplifting of lamellae might be due to infiltration of fluid between epithelium and basement membrane which ultimately increase diffusion distance for gas exchange. These findings were also found to be in agreement with Santos et al (2014), Fernandes et al (2007) and Ezemonye and Ogbomida (2010). Similar anomalies were seen by Liebel et al (2013) in Oreochromis niloticus and Astyanax aff.…”
Section: Resultssupporting
confidence: 86%
“…It is quite evident that the damage caused to the gills results in impairments in gaseous exchange capacity of the gills, which ultimately lead to respiratory distress. The gills showing hyperplasia and fusion in this study, similar alterations in the gills have also been reported in the fishes exposed to metals [32] [33] [34] and organic contaminants [35] [36] [37] for the damage of gills in the fish treated with toxicants. The kidneys of fish exposed to diazinon showed histological changes after long time exposure of 28 days of treatment such as hyperplasia of hematopoietic cells and interstitial congestion.…”
Section: Discussionsupporting
confidence: 87%